2019
DOI: 10.5534/wjmh.180123
|View full text |Cite
|
Sign up to set email alerts
|

Penile Prosthesis Infection: Myths and Realities

Abstract: Penile prosthesis infection is the most significant complication following prosthesis implant surgery leading to postoperative morbidity, increased health care costs, and psychological stress for the patient. We aimed to identify risk factors associated with increased postoperative penile prosthesis infection. A review of the literature was performed via PubMed using search terms including inflatable penile prosthesis, penile implant, and infection. Articles were given a level of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 79 publications
1
27
1
1
Order By: Relevance
“…in cases of urethral atrophy). Similar findings have been seen in the inflatable penile prosthesis literature as there is level II evidence that revision surgery increases the risk of infection [ 12 ]. However, the etiology of device failure in the revision AUS surgery population is likely a “multiple-hit” phenomenon related to a combination of prior tissue manipulation in addition to one or more comorbidities which impair small vessel function (diabetes, coronary artery disease, smoking status, and prior radiotherapy).…”
Section: Discussionsupporting
confidence: 82%
“…in cases of urethral atrophy). Similar findings have been seen in the inflatable penile prosthesis literature as there is level II evidence that revision surgery increases the risk of infection [ 12 ]. However, the etiology of device failure in the revision AUS surgery population is likely a “multiple-hit” phenomenon related to a combination of prior tissue manipulation in addition to one or more comorbidities which impair small vessel function (diabetes, coronary artery disease, smoking status, and prior radiotherapy).…”
Section: Discussionsupporting
confidence: 82%
“…However, use of a razor for hair removal compared to use of clippers was associated with an increase in postoperative infection (relative risk = 2.09, 95% confidence interval = 1.15–3.80). It is also important to notice that, although the 2016 ICSM guidelines recommend the use of an alcohol-based skin prep prior to IPP placement [16], the studies we found are discordant and did not show the superiority of a disinfectant on the others [17, 18]. Further research is needed into the standardization of pre-, peri-, and postoperative measures: guidance on these measures needs to be clear to both surgeons and patients.…”
Section: Resultsmentioning
confidence: 89%
“…It is commonly believed that some trivial measures like adequate hygiene, local application of ice, and the use of suspensory or wrap-around underwear may help to reduce the risk of PPI. A recent review by Hebert and Kohler [16] examined multiple preoperative/intraoperative factors evaluating their influence on the risk of PPI and divided them into elements that increase the risk, elements that reduce the risk, and elements that do not influence the risk. They used the 2011 Oxford Center for Evidence-Based Medicine Guidelines to give each conclusion a level of evidence (from Level 1 that means strongest evidence to Level 5 that represents weaker evidence).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these improvements, the possibility that the insertion of a prosthesis could lead to dangerous and harmful maneuvers still exists. We have to consider that the particular weakness of the cavernous and perineal tissues such as may occur after pelvic surgery or radiation therapy, the structural alterations in Peyronie's Disease (PD) and the presence of comorbidity such as Diabetes Mellitus (DM) or Coronary Artery Disease (CAD) continue to make Penile Prosthetic Surgery (PPS) a risky surgery (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%